L‐quebrachitol Modulates the Anti‐convulsant Effects of Carbamazepine Possibly Through Voltage‐gated Sodium Channel Blocking Mechanism in Chicks: In Vivo and In Silico Studies - Asifa Asrafi; Mohammad Aslam; Ali G. Alkhathami; Md. Sakib Hossain; Imam Hossen Rakib; Md. Sakib Al Hasan; Feroz Khan Nun; Md. Faisal Amin; Muhammad Torequl Islam (Brain and Behavior)
ABSTRACT Introduction L‐Quebrachitol (LQB), a naturally occurring bioactive compound, exhibits anti‐inflammatory, anti‐oxidant, anti‐cancer, and anti‐diabetic properties. However, its therapeutic potential in convulsant management remains largely unexplored. The objective of this study was to investigate the anticonvulsant effects of LQB in an In Vivo model and to examine its molecular interactions via In Silico docking simulations. Methods In the In Vivo study, pentylenetetrazol (PTZ) was administered intraperitoneally (i.p.) at 80 mg/kg to induce convulsions, and the test animals were treated orally with three doses of LQB (1, 5, and 10 mg/kg), with carbamazepine (CBZ) at 80 mg/kg as a standard drug. Results The results indicated that LQB at all tested doses significantly (p < 0.05) prolonged seizure latency and decreased convulsion frequency, with the 10 mg/kg dose showing the most significant effects. Furthermore, the combination of LQB (10 mg/kg) and CBZ (80 mg/kg) resulted in a synergistic increase in anticonvulsant activity. In the In Silico study, molecular docking analysis revealed that both LQB and CBZ interacted with the voltage‐gated sodium channel (VGSC), a key receptor involved in convulsions, with LQB demonstrating a binding affinity (BA) of −5.4 kcal/mol, which was moderate compared to CBZ's BA. Conclusion LQB showed potential anti‐convulsant activity in PTZ‐induced convulsion animals, possibly through blocking sodium channel receptors. Further studies are needed to clarify its mechanisms and clinical potential in convulsion treatment.